(untitled) (Journal of the College of Education for Women, 2018)
There are many studies that discussed the famous museum’s graveyards in the Islamic worlds, to study the lives of these figures, there are many difficulties for their studies because the first we need the regularity and history information, and many sciences support, such as in language, geography information. I am studying the research from Maraqid Al-Maaraf book by Harz Aldeen, the book has large members about the persons have graved in Persian Country in the middle ages, there are more than (30) figures in my study, I have studied every figure in this research depending on the sources and references books.